1994
DOI: 10.1080/14640749408401112
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Clock: Electroencephalographic Evidence for Oscillatory Processes Underlying Time Perception

Abstract: It has been proposed that temporal perception and performance depend on a biological source of temporal information. A model for a temporal oscillator put forward by Treisman, Faulkner, Naish, and Brogan (1990) predicted that if intense sensory pulses (such as auditory clicks) were presented to subjects at suitable rates they would perturb the frequency at which the resulting pattern of interference between sensory pulse rates and time judgments would depend on the frequency of the temporal oscillator and so m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 19 publications
3
72
0
1
Order By: Relevance
“…More sophisticated variations of this model accommodating for the complexity of biological systems have been suggested by Treisman and colleagues (see Treisman et al, 1990Treisman et al, , 1994. For example, different arousal or emotional states, or sensory inputs may affect the pacemaker function by perturbing its characteristic output frequency which in turn might slow or speed up the internal clock function and cause over-or underestimation of time (see Treisman et al, 1990Treisman et al, , 1994. We hypothesize that in DD the pacemaker may commonly tick normally.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…More sophisticated variations of this model accommodating for the complexity of biological systems have been suggested by Treisman and colleagues (see Treisman et al, 1990Treisman et al, , 1994. For example, different arousal or emotional states, or sensory inputs may affect the pacemaker function by perturbing its characteristic output frequency which in turn might slow or speed up the internal clock function and cause over-or underestimation of time (see Treisman et al, 1990Treisman et al, , 1994. We hypothesize that in DD the pacemaker may commonly tick normally.…”
Section: Discussionmentioning
confidence: 86%
“…Briefly, depending on a sensory arousal centre, the pacemaker usually produces ticks/pulses at a constant basic characteristic rate/frequency (Treisman et al, 1990(Treisman et al, , 1994 and sends them to a counter (i.e., the accumulator). Comparing the values in the counter with the reference duration stored in memory, determines the behavioural response.…”
Section: Discussionmentioning
confidence: 99%
“…Such a model could account for the present results if it were assumed that the learning occurred at the second stage, perhaps attributable to a reduction in variability, and that there were independent first-stage oscillators dedicated to different base frequencies. In partial support of these assumptions, Treisman et al (1994) reported electroencephalographic evidence of multiple first-stage oscillators.…”
Section: Models Of Temporal Processingmentioning
confidence: 93%
“…The neural circuitry proposed by Gray to carry out this process includes the cingulate cortex, and the cycle time was suggested to be of the order of 100 ms. Significantly, Treisman, Cook, Naish and MacCrone (1994) found evidence that the normal 'tick rate' of the internal clock was approximately 80 ms. The similarity between these values invites the speculation that the two cycles may in fact be one and the same.…”
Section: Discussionmentioning
confidence: 97%